2003
DOI: 10.1029/2003gl018024
|View full text |Cite
|
Sign up to set email alerts
|

Integrated parameterization of irrigation in the land surface model ORCHIDEE. Validation over Indian Peninsula

Abstract: [1] The work presented here describes a new modeling infrastructure of irrigation which is integrated in a land surface model and which will make this model a suitable tool for studies of interactions between irrigation water use and climate change. The model is presented and validated off-line over the Indian Peninsula. Numerical experiments are conducted with a 1 degree spatial resolution land surface model. Two 2-year simulations, forced by the ISLSCP (1987 -88) data sets, are conducted with and without irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 10 publications
(18 reference statements)
2
112
0
Order By: Relevance
“…The development of LSMs can be traced back to early work by Thornthwaite and Mather (1957) and Manabe (1969), who developed a simple "bucket model" based on the concepts of Budyko (1965). Early LSMs used simple parameterizations for solving surface energy and water balances without explicitly simulating the influence of land use change and human water management on surface hydrological processes (Deardorff, 1978;Bonan, 1995). They are used to estimate the exchange of energy, heat, and momentum between the land surface and atmosphere in GCMs, and to close budgets.…”
Section: Evolution Of Representing Human Impacts In Hydrological Modelsmentioning
confidence: 99%
“…The development of LSMs can be traced back to early work by Thornthwaite and Mather (1957) and Manabe (1969), who developed a simple "bucket model" based on the concepts of Budyko (1965). Early LSMs used simple parameterizations for solving surface energy and water balances without explicitly simulating the influence of land use change and human water management on surface hydrological processes (Deardorff, 1978;Bonan, 1995). They are used to estimate the exchange of energy, heat, and momentum between the land surface and atmosphere in GCMs, and to close budgets.…”
Section: Evolution Of Representing Human Impacts In Hydrological Modelsmentioning
confidence: 99%
“…Further new developments include consideration of the relevance of agriculture, wetlands and lakes for the aggregate behaviour of the land surface (e.g. Rosnay et al, 2003;Ringeval et al, 2012;Webler et al, 2012;Drewniak et al, 2013). With these aspects adding ever-increasing complexity, however, a new modelling strategy is required to ensure that the uncertainties do not spiral out of control as more and more uncertain parameters are introduced.…”
Section: Bounding Complexity: the Use Of Multiple Constraintsmentioning
confidence: 99%
“…Modeling studies have reported different magnitudes of irrigation cooling effects, depending on the irrigation schemes prescribed in their models (Qian et al 2013;Ozdogan et al 2010;Sacks et al 2008;Sorooshian et al 2011;Lo and Famiglietti 2013;Adegoke et al 2003;de Rosnay et al 2003;Haddeland et al 2006;Kanamaru and Kanamitsu 2008;B. Yang et al 2016).…”
Section: A Backgroundmentioning
confidence: 99%